The neuropathic potential of anti-GM1 autoantibodies is regulated by the local glycolipid environment in mice. - Greenshields, K; Halstead, S; Zitman, F; Rinaldi, S; Brennan, K; O'Leary, C; Chamberlain, L; Easton, A; Roxburgh, J; Pediani, J; Furukawa, K; Furukawa, K; et al. (2009)
Anti-GM1 ganglioside autoantibodies are used as diagnostic markers for motor axonal peripheral neuropathies and are believed to be the primary mediators of such diseases. However, their ability to bind and exert pathogenic effects at neuronal membranes is highly inconsistent. Using human and mouse monoclonal anti-GM1 antibodies to probe the GM1-rich motor nerve terminal membrane in mice, we here show that the antigenic oligosaccharide of GM1 in the live plasma membrane is cryptic, hidden on surface domains that become buried for a proportion of anti-GM1 antibodies due to a masking effect of neighboring gangliosides. The cryptic GM1 binding domain was exposed by sialidase treatment that liberated sialic acid from masking gangliosides including GD1a or by disruption of the live membrane by freezing or fixation. This cryptic behavior was also recapitulated in solid-phase immunoassays. These data show that certain anti-GM1 antibodies exert potent complement activation-mediated neuropathogenic effects, including morphological damage at living terminal motor axons, leading to a block of synaptic transmission. This occurred only when GM1 was topologically available for antibody binding, but not when GM1 was cryptic. This revised understanding of the complexities in ganglioside membrane topology provides a mechanistic account for wide variations in the neuropathic potential of anti-GM1 antibodies.